Seasonal breeding effects on productivity - Peacock, C.P. (International Livestock Centre for Africa, 1982)
A study conducted to assess the seasonal breeding effects on productivity of sheep and goats on the Maasai group ranch at Elangata Wuas in Kenya. Examines reproductive performance, mortality, growth and productivity. Includes data on parturition intervals, causes of pre-weaning mortality and production indices in the Maasai pastoral system. Shows potential improvement pathways.